On History of Soviet Historical Science Development in 1930—1940-ies: A. V. Mishulin’s Doctoral Thesis Defence - Skvortsov, A. M. (Nauc̆nyj dialog (Online), 2019)
The article analyzes the information on the preparation and defense in 1943 of A. V. Mishulin’s doctoral thesis “Ancient Spain and its entry into the struggle for independence (before the establishment of the Roman provincial system in 197 BC.” The attention is paid to the regulatory framework of protection of dissertations, the preparation of the dissertation debate and the procedure of its holding in 1940-ies. The article presents the results of comparative analysis of Mishulin’s autobiographies of different years (1920-1930-ies and 1943), which allows to identify the factors of formation of his “canonical” biography. It is proved that the applicant tries to show himself as a “real scientist” (not a “nominee”) who has passed all the necessary stages of scientific “growing up.” It is shown on the basis of archival data that the applicant regarded the defense of his doctoral thesis as a kind of ritual that would allow him to gain credibility among famous historians and become a full member of the scientific community, which could not be achieved in connection with the publications (in particular, the monograph on the uprising of Spartacus), which were published before the defense of the thesis. Attention is paid to the scientific style of A. V. Mishulin, which is characterized by broad historiographical reviews, generalizations based on them, following the findings of historiography. It is noted that, despite the military conditions, from a formal and substantive point of view, the dispute over the defense of the thesis was almost perfect.